Neurosteroids as positive and negative allosteric modulators of ligand-gated ion channels: P2X receptor perspective - Sivcev, Sonja; Kudova, Eva; Zemkova, Hana (Neuropharmacology, 2023)
Neurosteroids are steroids synthesized de novo in the brain from cholesterol in an independent manner from peripheral steroid sources. The term "neuroactive steroid" includes all steroids independent of their origin, and newly synthesized analogs of neurosteroids that modify neuronal activities. In vivo application of neuroactive steroids induces potent anxiolytic, antidepressant, anticonvulsant, sedative, analgesic and amnesic effects, mainly through interaction with the γ-aminobutyric acid type-A receptor (GABAAR). However, neuroactive steroids also act as positive or negative allosteric regulators on several ligand-gated channels including N-methyl-d-aspartate receptors (NMDARs), nicotinic acetylcholine receptors (nAChRs) and ATP-gated purinergic P2X receptors. Seven different P2X subunits (P2X1-7) can assemble to form homotrimeric or heterotrimeric ion channels permeable for monovalent cations and calcium. Among them, P2X2, P2X4, and P2X7 are the most abundant within the brain and can be regulated by neurosteroids. Transmembrane domains are necessary for neurosteroid binding, however, no generic motif of amino acids can accurately predict the neurosteroid binding site for any of the ligand-gated ion channels including P2X. Here, we will review what is currently known about the modulation of rat and human P2X by neuroactive steroids and the possible structural determinants underlying neurosteroid-induced potentiation and inhibition of the P2X2 and P2X4 receptors. This article is part of the Special Issue on "Purinergic Signaling: 50 years".
Keywords: Neurosteroids; adenosintrifosfát; vazebná místa; Ligand-Gated Ion Channels; Receptors, Purinergic P2X; Brain; krysa rodu Rattus; Binding Sites; purinergní receptory P2X; Animals; Receptors, Purinergic P2X2; lidé; purinergní receptory P2X2; Humans; zvířata; Rats; mozek; Adenosine Triphosphate; iontové kanály řízené ligandy; neurosteroidy